The utilization of alfalfa that planted at Tobasa highland, North Sumatra for growing Boerka goat feed - Sirait, Juniar; Tarigan, A.; Simanihuruk, K. (Indonesian Animal Sciences Society, 2011)
Alfalfa (Medicago sativa L.) is a herbaceus legume which is potential to be used as goat feed for itâs high production and nutritive value. This research was aimed to study the adaptation of alfalfa planted at highland-moderate climate and itâs utilization for goat feed. This research concists of two activities, ie 1) Agronomy of alfalfa that adapted to highland as a goat feed resource, and 2) The alfalfa usage technology as goat feed. On the first activity alfalfa was planted on highland-moderate climate Gurgur, Tobasa District, North Sumatra Province. Data was collected included: growth percentage, morphology and production aspects, and nutritive value. The harvesting was conducted for three times, where the first cutting had done at 100 days after planting. Investigation of morphology characterirtics was done before alfalfa harvesting. The utilization of alfalfa as goat feed was carried out on the second activity which was arranged in a completely randomized design. Twenty male Boer x Kacang crossbredÂ (Boerka) goats of 5-6 months of age with average body weight 14.2Â±0.8 kg were randomly assigned to four feed treatments where each treatment consited of five replications. The four feed treatments were: P1 = 100% grass + 0% alfalfa; P2 = 90% grass + 10% alfalfa, P3 = 80% grass + 20% alfalfa, and P4 = 70% grass + 30% alfalfa. Data observation included dry matter intake, average daily gain, feed efficiency, and income over feed cost. Results showed that alfalfa growth percentage was 65% with good growth and high either production or nutritive value. The average shoot dry matter production was 438.6 g/m2 which was equivalent to 26.3 t/ha/yr. The crude protein content of alfalfa on the first, second and third harvesting were 17.93; 21.89 and 17.73 per cent, respectively. The utilization of alfalfa that had been processed to be crude-meal can be applied as goat feed. Supplementation of 70% grass and 30% alfalfa meal showed the best results: ADG 59.17 g/d, feed efficiency 0.14, and IOFC Rp 736/h/d. Key Words: Alfalfa, Herbage, Production, Meal, Feed, Goat